Peningkatan Penggunaan Moda Non-Motorized Transport dengan Stated Preference pada Pelajar Sekolah Menengah Negeri Jakarta Pusat - Argarisma, Afrian; Naipospos, Binsar Parasian (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2023)
The potential for daily trips made by students in DKI Jakarta reaches 3.8 million trips per day, or equivalent to one-fifth of all daily trips in DKI Jakarta. This study aims to look at the factors that influence student decisions when choosing school travel modes. The research sample was 573 public high school students in Central Jakarta with stratified random sampling. The method of analysis uses descriptive statistics and Multinomial Logit (MNL) with the variables stated and stated preferences. Factors that significantly influence the choice of mode of preference by public high school students in Central Jakarta are age, school level, pocket money, motorized vehicle ownership and driver's license, free bicycle facilities, Safe Routes for School facilities, school bus travel time, time spent on public transport, and private vehicle costs. The resulting model is able to influence the dependent variable by 41.4%, while the other 58.6% is influenced by independent variables outside of this study. The school zoning policy was able to convince 59% of students to switch modes to walking, while the free bicycle facility policy and RASS convinced 57.46% of students to switch modes by bicycle on school trips. Key Words: mode choice, non-motorized transport, school travel, multinomial logit, stated preference, transportation policy